Construction of complex nested ideal lattices for complex-valued channel quantization - Watanabe, C.C. Trinca (2018)
In this work we develop a new algebraic methodology which quantizes complex-valued channels in order to realize interference alignment (IA) onto a complex ideal lattice. Also we make use of the minimum mean square error (MMSE) criterion to estimate complex-valued channels contaminated by additive Gaussian noise.